Focusing on facilitation: Issues and challenges of capacity development in Indonesia’s social forestry reforms - Galudra, Gamma (Forestry Faculty, Universitas Hasanuddin, 2019)
As the Indonesian government sets a target to allocate 12.7 million ha of state forest land for social forestry in 2019, one of the most crucial [and overlooked] issues is the extent of capacity, knowledge, skills, and engagement of social forestry facilitators and the extension workers that support the government in meeting their targets on social forestry. In this short paper, I seek to reorient the discussion towards the main issues and challenges of social forestry capacity development in Indonesia. On the one hand, there are some promising achievements made by the government in the wake of social forestry policy design and implementation, particularly in their ability to expand the scope of targeted areas for social forestry designation, as well as the increase in the numbers of community business group established. On the other hand, however, there are some challenges that are evident. Coordination within the ministry remains a major barrier, and extends to coordination problems across and between sub-national governments. Furthermore, engagement with the private sectors and involvement of NGOs remains lacking. And finally, the distribution of social forestry facilitators and extension workers across the numerous social forestry sites in Indonesia, as well as the overall capacity development needs among facilitators continues to be a major hindrance in meeting targets. I conclude by highlighting that more attention needs to be devoted to the role and capacity of facilitators, and furthermore, that the government needs to address these challenges through various institutional reforms and methods on social forestry training, as well as developing more rigorous training modules for community facilitators.